Yahoo Web Search

1. Sort by

1. Find a unit vector with a negative i component that is orthogonal to both i + j and i + k.?

(1/√3)(- i + j + k)

2 Answers · Science & Mathematics · 18/06/2019

2. How do Prove this? I don't even know how to approach this problem. Any help is appreciated.?

... to rewrite the equation for the parabola in vertex form: y = (x - h)² + k We have: y = x² + 6x + 10 To complete the square: a. Take...

2 Answers · Science & Mathematics · 15/06/2019

3. write an equation for the parabola with vertex (-5,1) and directrix x=-7/2?

Vertex (h,k) = (-5,1) -p = Distance from the vertex to the directrix = -5+7/2 p = -3/2 4p...

3 Answers · Science & Mathematics · 17/06/2019

4. please help me solve this assignment my day of submition is fast approaching?

...θ + 1)2 + 1 (i) y = x² + 1 Vertex form: y = 4p(x−h)² + k → y = (x−0)² + 1 (ii) Focus = (h, k+p) (iii) Vertex = (h...

3 Answers · Science & Mathematics · 15/06/2019

5. Roots and Coefficients of polynomial equations two roots of x^3 + mx^2 - 3x - 18 are equal and rational, Find m please?

...ka^2 + ja + l) a^3 + 3a + 36 = ka^3 + ja^2 + la + 3ka^2 + 3ja + 3l a^3 = ka^3 1 = k 0a^2 = ja^2 + 3ka^2 0 = j + 3k 0 = j + 3 j = -3 la + 3ja = 3a l + 3j = 3 l - 9...

3 Answers · Science & Mathematics · 15/06/2019

6. Calc Help?

...subject to (x-2)^2 + y^2 - 2 = 0 We form L(x,y) = x^2 + (y-14)^2 - k( (x-2)^2 + y^2 - 2 ) Diff wrt k Lk = (x-2)^2 + y^2 - 2 = 0...

1 Answers · Science & Mathematics · 14/06/2019

7. exponetial?

...approximately equal to 2.71828 t is the amount of time (in this case years) k is the decay (or grown if positive) constant. Looking at the graph...

3 Answers · Science & Mathematics · 13/06/2019

8. I need help with this question. Any help is appreciate! Use mathematical induction to prove that 4n - 1 is divisible by 3 for all n >= 1?

... it to 4^(n) - 1 = 3k and assign no real values to n or k and we have the same basic form. And since 4^(n) - 1 is divisible by 3...

2 Answers · Science & Mathematics · 14/06/2019

9. What is the pattern equation for set builder notation for Question 2b?

All the terms are 1 more than a multiple of 6. So here's a possible way to write this in set builder notation. {6k+1, k∈ℤ}

2 Answers · Science & Mathematics · 12/06/2019

10. Mathematical Proof: wi is in the Span{v1,..,vr} for each I=1,..s, then proof Span{v1,..,vr} = Span{v1,..,vr, w1,..,ws}?

...s is span {w1, w2,...,ws} = k1v1 + k2v2 +....+ ksvs where k1, k2,...,ks are any real numbers. So we see that Span{v1,..,vr...

1 Answers · Science & Mathematics · 11/06/2019